The Effect of Propolis Honey on Leukocyte Levels in Wound Healing During the Inflammatory Phase of Second-Degree Perineal Rupture (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Propolis honey has long been recognized as a natural alternative treatment with multiple health benefits, particularly in accelerating wound healing. Its bioactive components, such as flavonoids, exhibit strong antioxidant and anti-inflammatory properties that help stabilize reactive oxygen species (ROS), thereby reducing free radical activity and mitigating inflammatory reactions. This study investigated the effect of propolis honey administration on leukocyte levels during the wound-healing process in postpartum mothers with second-degree perineal rupture. A quasi-experimental design was employed, involving 44 postpartum mothers divided into two groups: 22 in the control group and 22 in the intervention group. Respondents were selected through randomization, and data collection included demographic information, food consumption patterns, and leukocyte levels. Univariate analysis was conducted to examine changes in leukocyte levels before and after treatment, while bivariate analysis assessed differences between the control and intervention groups. Findings revealed that the intervention group, which received propolis honey, experienced a greater average decrease in leukocyte levels (-6.6255 ± 4.78086 /uL) compared to the control group (-6.1691 ± 5.57134 /uL). The reduction in leukocyte count among the intervention group is attributed to the presence of flavonoids in propolis honey, which play a crucial role in regulating immune response and controlling inflammation. This process supports faster tissue repair and reduces the risk of infection. The study concludes that propolis honey administration has a measurable effect on lowering leukocyte levels in postpartum mothers suffering from second-degree perineal rupture. Future research is encouraged to differentiate between spontaneous rupture and episiotomy cases, as well as to measure wound surface area for more precise evaluations. The findings support the potential integration of propolis honey into postpartum wound management protocols as a safe, natural, and effective complementary therapy.